COMPARATIVE STUDY OF LAW: WARALABA DALAM PERSPEKTIF PERJANJIAN - Andi Fariana* (Perbanas Institute, 2021)
Franchising is a form of business activity that is quite growing and in demand. The legal fundamentals of franchising are formed in agreements and in Government Regulation Number 42 of 2007, sufficiently regulated that there must be consideration for making a franchise agreement, but to find out what the form of the agreement is, the peculiarities and strengths of the validity of both conventional franchises and sharia franchises, an investigation and studies performed so that it is found that the aspects of the agreement regulated in Government Regulation Number 42 of 2007 as well as those regulated in the Civil Code (KUHPerdata) are the guidelines and legal umbrella for the franchise agreement made. According to the Civil Code, Agreement Law is open in nature and the agreement made will become law for the parties involved as long as it is made on the basis of an agreement. Thus, a franchise agreement made on the basis of Islamic Law (whether in the form of a syirkah / cooperation agreement or an ijarah / lease agreement with certain rewards) does not contradict with the principles of the agreement contained in the Civil Code and which are regulated in Government Regulation No. 42 of 2007. The most important thing is that the parties agree and the agreement made is not an agreement on the object of the franchise that is contrary to sharia.